Efektivitas Distribusi Zakat Produktif dalam Meningkatkan Kesejahteraan Mustahik di Yayasan Baitul Maal PLN Unit Induk Wilayah Sumatera Utara - Hanif, Hilman; Soemitra, Andri (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
In the Qur'an, the words zakat and prayer are often found together. According to the scholars, zakat is the same the importance of prayer. Zakat, according to some historians and Islamic scholars, functions to encouraging Muslims to be able to maintain their faith in Allah SWT in a better way economic income. The aim of this research is to determine the implementation of the distribution of productive zakat funds which was carried out at YBM PLN UID North Sumatra. Qualitative method with a descriptive analytical approach used to understand the phenomenon of productive zakat comprehensively. In this research, the purposive method sample and snowball sampling were applied to identify informants, with a focus on amil in YBM PLN UIW North Sumatra. The results of the analysis show that the management of zakat is productive by the zakat amil plays a crucial role in ensuring the distribution of zakat is right on target and effective. There is a system transparent and accountable in the management of zakat funds, competent selection of amil, and use Information technology is an important factor in ensuring the success of productive zakat programs.